Free and French in the Caribbean : Toussaint Louverture, Aimé Césaire, and Narratives of Loyal Opposition - Walsh, John Patrick, 1971- (Book collections on Project MUSE., 2013)
This book explores the writings of Toussaint Louverture and Aime Cesaire to examine how they conceived of and narrated two defining events in the decolonializing of the French Caribbean: the revolution that freed the French colony of Saint-Domingue in 1803 and the departmentalization of Martinique and other French colonies in 1946. The author emphasizes the connections between these events and the distinct legacies of emancipation that emerged through the narratives of revolution and nationhood passed on to successive generations.